The differential duels - Jačiauskas, I. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. П. Ячаускас. Дифференциальные игры типа дуэлиI. Jačiauskas. Dvikovos tipo diferencialiniai lošimai